(untitled) (Northern International Medical College Journal, 2015)
Background : The polycystic ovary syndrome is a common cause of infertility. Clomiphene is the current first-line infertility treatment in women with the polycystic ovary syndrome. Objective : To observed effect of clomiphene therapy in infertile women with polycystic ovary syndrome. Methodology : In this cross-sectional study we enrolled 210 infertile women aged 25 35 years diagnosed as polycystic ovary syndrome. Participants who had normal urine cavity and sperm concentration of at least 20 million/ml of her husband were prescribed clomiphene for 6 months. Medication was discontinued when pregnancy was confirmed and participants were followed until delivery. Results : After 6 months treatment 85(40.5%) patient was conceived. Live birth was 44(20.9%) of 210 subjects. Among pregnancies multiple (twin) birth was 12(5.7%). First trimester pregnancy loss was 41(19.5%). After having 6 months of therapy there was no pregnancy in125 (59.5%) patients. Conclusions : Clomiphene is safe and cost effective medicine in achieving live birth in infertile women with polycystic ovary syndrome. Northern International Medical College Journal Vol.7(1) Jul 2015: 94-96